Alcune annotazioni sui manoscritti di contenuto medico copiati dal Monaco Atanasio: I codici Parisinus Graecus 2193, Athos Vatopedi A 29 E Vindobonensis Medicus Graecus 6 - Calà, Irene (Collectanea Philologica, 2023)
The copyist Athanasios monk was in the mid-15th century active in copying numerous manuscripts, some of them on medical topics. Among them, three pass on the sixteen Libri medicinales of Aetius Amidenus, lived in 6th century and one of most important authors for medicine in late antiquity. Among these, two are complete copies made by Athanasius, the manuscript now in Paris and the one at the Mount Athos, but in the case of the Vienna manuscript, which dates back to the 14th century, he was the restorer. By reading these Aetius manuscripts, it was possible to rediscover some fragments of Philagrius, an author lived probably between 3th and 4th century. Among the numerous marginalia in Athanasius’s own hand, new fragments have thus been identiﬁed that can be attributed to Philagrius, whose works have come down to us only through indirect tradition, as well as a short passage from the tenth book of Galen’s treatise De anatomicis administrationibus, which is lost in Greek.